Mechanisms of phase formation along the synthesis of Mn-Zn ferrites by the polymeric precursor method - Martins, Murillo Longo [UNESP]; Florentino, Ariovaldo de Oliveira [UNESP]; Cavalheiro, Alberto Adriano; Silva, Rafael Innocenti Vieira da [UNESP]; Santos, Dayse Iara dos [UNESP]; Saeki, Margarida Juri [UNESP] (Elsevier B.V., 2014)
Considering the wide application of crystalline Mn-Zn ferrites microparticles, understanding synthesis routes that allow the achievement of such materials is a constant need. In this work, Mn-Zn ferrites, Mn(1-x)ZnxFe2O4 (0.15 <= x <= 0.30), were synthesized by the polymeric precursor method in well-cohtrolled steps and the mechanisms of phase formation under different thermal treatments were studied. Such investigation was performed by means of thermal analysis (TG/DTA), synchrotron X-ray powder diffraction (SXPD) (including in-situ and anomalous scattering experiments) and scanning electron microscopy (SEM). The ferrite precursor powders present the spinel as single crystalline phases whose cell parameters increase as Mn is substituted by Zn, indicating possible Fe deficiencies into the structure. The crystallization degree of these samples is also affected by the Mn substitution and reaches a maximum for x=0.25. Further thermal treatments in air at 700 degrees C and 1100 degrees C lead to additional events also related to the Zn content, such as carbonates elimination and crystallization of the contaminant phase hematite. Thermal treatments under N-2 atmosphere at 700 degrees C allow the achievement of powders with only the spinel phase, especially for x=0.25 for which highly crystalline and homogeneous ferrite is obtained despite the Fe deficiency determined by anomalous scattering SXPD. Finally, thermal treatments at 1100 degrees C under N-2 atmosphere jeopardize the stability of the spinel structure and lead to hematite precipitation. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Mn-Zn ferrites; Polymeric precursor method; X-ray diffraction; Thermal analysis